Efektivitas Media Pembelajaran Digital Dalam Meningkatkan Motivasi Belajar Siswa di SDN 2 Selat Kabupaten Kapuas - AHMAD BAIHAQI; Dina Amelia; Khamsatun; Noor Azizah; Nor Sa’adah (AL-IBNOR, 2026)
This study aims to determine the effectiveness of digital learning media in improving student learning motivation at SDN 2 Selat Hulu Kuala Kapuas. The study used a qualitative method with a case study approach. The subjects were teachers and sixth-grade students at SDN 2 Selat Hulu Kuala Kapuas. Data collection techniques were observation and interviews. The results showed that the use of digital learning media, such as instructional videos, PowerPoint presentations, illustrative images, and interactive platforms, significantly impacted student learning motivation. Digital media created a more interactive, enjoyable, and visual learning environment, thereby increasing student attention, enthusiasm, and active participation in the learning process. Students felt more enthusiastic, less bored, and grasped the material more quickly due to the engaging presentation through clear visuals and audio. The consistency between the results of interviews, observations, and data analysis strengthens the conclusion that digital learning media positively contributes to improving student learning motivation. This study recommends the use of digital media in a well-structured and well-scheduled manner to optimize its benefits in supporting optimal learning outcomes.